2014
DOI: 10.1002/j.0022-0337.2014.78.5.tb05721.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental Student Perceptions of the Educational Value of a Comprehensive, Multidisciplinary OSCE

Abstract: The aim of this study was to examine student perceptions of the educational value of a comprehensive, multidisciplinary objective structured clinical examination (OSCE). The examination is administered after the second year of the curriculum, prior to the beginning of clinical training at the Columbia University College of Dental Medicine. The quantitative component of the study consisted of a survey administered to students who had taken the OSCE (N=78). Due to the ordinal level of data produced by the Likert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 21 publications
5
29
0
6
Order By: Relevance
“…Various studies have revealed that students' interest in learning leads to greater degree of skill acquisition. [6][7][8] Similarly, students' level of perception towards OSCE had statistically significant association with evidenced based learning (p=0.041). It states that 55.6% of students always utilized evidenced based learning, in comparison with students who sometimes utilized evidenced based learning as it is a scientific method of evaluation which play vital role in order to enhance learning retention and help to give clear clarity with scientific reason during learning.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have revealed that students' interest in learning leads to greater degree of skill acquisition. [6][7][8] Similarly, students' level of perception towards OSCE had statistically significant association with evidenced based learning (p=0.041). It states that 55.6% of students always utilized evidenced based learning, in comparison with students who sometimes utilized evidenced based learning as it is a scientific method of evaluation which play vital role in order to enhance learning retention and help to give clear clarity with scientific reason during learning.…”
Section: Discussionmentioning
confidence: 99%
“…As habilidades de comunicação puderam ser observadas na realização das estações da Semiologia, nas quais o aluno interagiu com um paciente simulado para obter informações importantes no diagnóstico da doença pela sintomatologia e na abordagem do paciente para a tomada radiográfica na estação de Radiologia. O OSCE pode ser usado para avaliação de várias competências e habilidades de conteúdos associados ou isolados 22 . Pode-se avaliar, por exemplo, os componentes curriculares pré-clínicos de um determinado termo ou ano letivo como utilizado em nosso estudo, ou então como relatado por Höfer et al 19 (2013) que aplicaram o OSCE em Cirurgia Bucomaxilofacial, com 10 estações avaliando competências e habilidades distintas dessa área.…”
Section: Discussionunclassified
“…Apesar de não ter sido realizado nenhum questionário para verificação de ansiedade, foi observado, por relato espontâneo, o nervosismo e a ansiedade de grande parte dos alunos, o que pode ser explicado pelo ambiente da própria avaliação e por ser a primeira vez que eles estavam entrando em contato com esse tipo de exame. No entanto, relataram que o OSCE é uma avaliação mais objetiva e aproximada da realidade de atividade clínica, o que corrobora com a literatura 22,28 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A aplicação do OSCE apresenta grande parte dos critérios de uma boa avaliação, como validade (afere o grau no qual o teste realmente avalia aquilo que propõe), confiabilidade (afere a reprodutibilidade e a consistência de um teste) e viabilidade (promoção de resultados e feedback, produzindo melhor suporte educacional) 17,18 . Além de avaliar a competência clínica dos estudantes, o método OSCE permite a autoavaliação por parte dos alunos, assim como um momento de devolutiva dos resultados e discussão com o professor.…”
Section: Introductionunclassified